The Action on Blood Clotting of Different Lipoid Fractions of Beef Brain* (Methods of Fractionization and Chromatographic Isolation Procedure of a Phospholipid Anticoagulant) - Kahn, M. J. P; Hans, M; Bourgain, R. H (Thrombosis and Haemostasis, 1965)
A method of fractionation and isolation of a lipid anticoagulant from beef brain has been described. This method is based on chemical and chromatographic techniques. The lipid anticoagulant was found to be an inositol monophosphatide containing two different fatty acids. The anticoagulant activity has been evidenced in the Russell-viper-venom test and is believed to interfere with the formation of the early intermediate products involving factor X.